Derivation and Validation of a Prognostic Model for Mortality in Chinese Patients with Acute Pulmonary Embolism - Jiarui Zhang MD; Adila Ali MD; Yu Liu MD; Lige Peng MD; Jiaqi Pu MD; Qun Yi MD PhD; Haixia Zhou MD PhD (Clinical and Applied Thrombosis/Hemostasis, 2022)
Introduction We aim to explore the risk factors for in-hospital mortality and to derive a prognostic model for patients with APE in China. Materials and methods Inpatients with APE were enrolled from West China Hospital between January 2016 and December 2019. Logistic regression analyses were used to explore risk factors for in-hospital mortality and develop a prognostic model. Results A total of 813 subjects with APE were included in this study, of whom 542 were in the training set and 271 were in the test set. Multivariable regression analyses indicated that age, male, heart rate, systolic blood pressure, elevated NT-proBNP or troponin T, malignancy, chronic renal insufficiency, and respiratory failure were independent risk factors for in-hospital mortality. For the training set, the area under the curve (AUC) of the ROC curve was 0.899, with a sensitivity and specificity of 89.7% and 77.7%, respectively. The model had higher prediction accuracy than the PESI and sPESI. Conclusions The prediction model has proven excellent discrimination and calibration, which may be a useful tool to help physicians make decisions regarding the best treatment strategy.